JUSTIFICATION FOR THE ESTABLISHMENT OF A LAND COURT IN INDONESIA: REALIZING JUSTICE IN LAND DISPUTE RESOLUTION - Wahid, Abdul; Sulistiyono, Adi (Masalah-Masalah Hukum, 2025)
Agrarian disputes in Indonesia are highly complex, covering a range of issues such as customary and communal land rights, certificate disputes, conflicts between communities and corporations, and state land acquisition. These challenges are compounded by the inability of general courts to effectively address them due to overlapping jurisdictions, inadequate coordination, and a lack of technical expertise. Consequently, the resolution of land disputes is often delayed, leading to diminished public trust in the judicial system. Comparative studies from Brazil and New Zealand have shown that specialized land courts can enhance efficiency, consistency, and the protection of indigenous rights by focusing on specific mandates, employing expert knowledge, and utilizing mediation mechanisms. This research highlights the urgent need for the establishment of a Land Court in Indonesia, presenting it as a critical institutional reform that would ensure legal certainty, provide substantive justice, and improve access to justice. The novelty of this study lies in its integrative approach, which combines doctrinal, comparative, and empirical analyses. The proposed Land Court, staffed with specialized judges, land experts, and supported by strong mediation procedures, is designed to offer quicker, fairer, and more socially legitimate outcomes. This approach is expected to strengthen public confidence in Indonesia’s land governance system, ultimately improving the overall effectiveness of land dispute resolution.